Mechanism of Mongolian Medicine Eerdun Wurile in Improving Postoperative Cognitive Dysfunction Through Activation of the PI3K Signaling Pathway - Lv, Zhixin; Che, Limuge; Du, Yiri; Yu, Jianshe; Su, Enboer; Liu, Hui; Chen, Dongmei (Frontiers in Neuroscience, 2022)
Objective To study the effect of Eerdun Wurile (EW), a traditional Mongolian medicine, on the cognitive function of rats by activating the IRS-PI3K-AKT-GLUT4 pathway in an animal model of postoperative cognitive dysfunction (POCD). Methods Fifty clean-grade adults Sprague Dawley (SD) male rats were assigned to one of five groups: (1) a control group with no anesthesia (Group C), (2) a POCD model group with anesthesia only (Group P), (3) POCD group with low-dose EW treated (Group L), (4) a POCD group with high-dose EW treated (Group H), and (5) a POCD model group with dexmedetomidine treated (Group D) for positive control. The study started 7 days after all rats had acclimated to housing. Rats were trained in the Morris Water Maze navigation 5 days before surgery. All rats underwent the same maze for navigation and spatial exploration experiments on the preoperative day 1 and postoperative days 1, 3, 5, and their learning and memory abilities were assessed. At the end of the water maze experiment, rats were sacrificed to obtain hippocampal tissue. The mRNA levels of IRS-2, PI3K, AKT, and GLUT4 were measured in the hippocampus by real-time PCR, and the expression of IRS-2, PI3K, AKT, and GLUT4 protein in the hippocampus was determined by Western blotting to investigate the potential mechanisms at the molecular level. Results Compared to control Group C, Group P, L, H, and D showed prolonged escape latency (P < 0.05) and decreased number of times to cross the platform (P < 0.05) at 1, 3 and 5 days after surgery. Compared to Group P, Group L, H, and D showed a decrease in escape latency with an increased number of crossing the platform at all-time points after surgery (P < 0.05). Within individual P, L, H, and D groups, escape latencies decreased (P < 0.05) and the number of times that the platform was crossed increased (P < 0.05) between postoperative days 3 and 5 compared to postoperative 1 day. Compared to Group C, the mRNA expression of IRS-2, PI3K, AKT and GLUT4 in the hippocampus of P, L, H, and D groups were decreased (P < 0.05). Compared to Group P, IRS-2, PI3K, AKT, and GLUT4 in the hippocampus of L, H, and D groups were increased (P < 0.05). Compared with Group D, the expression levels of IRS-2 and AKT in both L and H groups were higher. The expression level of PI3K in Group L was also higher (P < 0.05) vs Group D. The expression of AKT mRNA in Group H was higher than in Group L (P < 0.05). Compared to Group C, the p-IRS-2/IRS-2 ratio in the hippocampus of Group P was higher than that of Group C (P < 0.05). Compared to Group P, the ratios of p-IRS-2/IRS-2 in Group L, Group H, and Group D were lower, and the ratios of the p-PI3K/PI3K, p-AKT/AKT, and p-GLUT4/GLUT4 were higher (P < 0.05). Conclusion Administration of EW showed the effect on the signaling pathway in rats with POCD. The therapeutic effect was better in the low-dose group. This could be related to the insulin downstream signal molecule PI3K and the IRS-PI3K-AKT-GLUT4 signaling pathway.